COMMUNICATIVE APPROACH IN TEACHING ENGLISH GRAMMAR AMONG B1 EFL STUDENTS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article investigates the effectiveness of the communicative approach in teaching English grammar among B1 EFL students. The study mainly focuses on the grammar items when, if, and whether and examines how communicative activities influence students’ grammatical understanding and participation. In order to achieve the objectives of the research, an experimental study was conducted using a specially designed interactive technique called the “Doors” Method. The participants were divided into control and experimental groups, where different teaching approaches were applied. In addition, survey questionnaires and classroom observations were used to collect data regarding students’ perceptions of communicative grammar teaching. The findings of the study revealed that students taught through the communicative approach demonstrated higher participation, better understanding of grammar structures, and greater motivation compared to those taught through traditional methods. The results also indicated that communicative activities and real-life interaction contribute positively to grammar learning at the B1 level. Overall, the study confirms the effectiveness of communicative grammar teaching in EFL classrooms.
Keywords: communicative approach, grammar teaching, B1 EFL students, communicative language teaching, grammar instruction, Doors Method, English language learning.